MATHEMATICAL REPRESENTATION AND SELF CONFIDENCE OF ELEMENTARY SCHOOL STUDENTS WITH AUDITORY INTELLECTUALLY REPETITION LEARNING - nia Jusniani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Students' representational abilities and self-confidence have an important role because they can train students to improve their problem-solving skills in various forms including pictures, diagrams, mathematical expressions, as well as words or written text. In this study used quantitative research with the method of Quasi Experimental Design. The purpose of this study was to determine the mathematical representation ability and self-confidence of students using the Auditory Intellectually Repetition learning model with students using the ordinary learning model. The study was conducted in March 2019 and the population in this study were fifth grade students at SD Negeri 2 Ciranjang in the academic year 2018/ 2019. The sample in this study was selected by purposive sampling technique with class V-1 as the experimental class with 30 students and class V-2 as the control class with 30 students. The experimental class followed the learning model with Auditory Intellectually Repetition and the control class followed the conventional learning. The results of the research analysis show that (1) there are differences in students' mathematical representation abilities using the Auditory Intellectually Repetition learning model with students using the ordinary learning model. Students have a high self-confidence in learning mathematics by using the Auditory Intellectually Repetition learning model